Ett bra erbjudande? – När riskerar kampanjer att aktualisera reglerna om underprissättning? - Pettersson,Marielle (2019)
The prohibition against abuse of a dominant position, and thereby the prohibition against predatory pricing, is regulated in both the Treaty on the Functioning of the European Union and in the Swedish Competition Act. The prohibition is clearly formulated and it does not indicate that there is any form of undercutting that is allowed for companies in a dominant position. In Swedish literature of jurisprudence, however, a perception has emerged that certain forms of undercutting is allowed even for companies in a dominant position. It is actions that should not be considered to constitute abuse of the dominant position and therefore is to be allowed already for that reason. Thus, the Swedish literature of jurisprudence does not advocate that there is an exception to the statutory prohibition. The fact that the statutory prohibition is clear and unwavering, while the Swedish literature of jurisprudence advocates more or less extensive possibilities to avoid the prohibition, plus the fact that there is no case law relating to this specific issue, makes it hard för companies in a dominant position to know if any type of undercutting is allowed. This situation, I think, creates an uncertainty among the companies in a dominant position that do not favor the efficient competition on the market. In order to create an intelligibility for the companies in a dominant position at the market that allows them to determine where the boundary goes between permitted offers and predatory pricing, the Court of Justice of the European Union must clarify their case law. The most urgent matter is that the Court of Justice of the European Union gives a ruling on whether there are situations where a company in a dominant position may set prices below their cost without it is considered as predatory pricing, and also which circumstances that constitutes predatory pricing.
Keywords: EU-rätt; EU law; konkurrensrätt